A Clinical Study on Gridhrasi (Sciatica) with Special Reference to Ruk (Pain) and its Management with Krushna Churnam - Bharatilata, Acharya; Bihari, Khuntia Bipin (International Research Journal of Ayurveda & Yoga, 2025)
Low back pain is one of the most common diseases affecting 30% of patients attending the general outpatient department. It affects the people of all ages from young adults to elder one. Sciatica is the most appearing one among the low back disorder. It is a condition in which pain radiating along the sciatica nerve, which runs down one or both legs from the lower back. The pain in Sciatica sometimes hampers the person’s daily activities because of its intensity. Gridhrasi in Ayurveda is the best simulation of the disease Sciatica. In Gridhrasi, pain starts from Sphik (Hip) and runs down to Kati prustha (Low back), Uru (thigh), Jaanu (Knee), Jangha (calf), and Pada (foot) (Ref- Ch-28/56-57). Along with pain it may be associated with stiffness, heaviness based on doshik involvements. Pain being the primary symptom needs pain killers for its relief. Ayurveda has a good scope in managing the pain of Gridhrasi through oral medications as well as therapeutic procedures, such as Panchakarma. Here in this study, the medication that has been chosen is the Krushna churnam (Ref- B.R.26/53), which is applied on 25 patients of both genders at Gopabandhu Ayurveda Mahavidyalaya and Hospital, Puri along with another 25 patients were given the control drug Etoricoxib molecule in a Randomized controlled clinical trial method. After 30 days, the results obtained are encouraging, such as 72% got maximum improvement in trial drug and 68% in control drug.